The effect of the dental health training on the pattern of guidance tot brush your teeth by parents of first- class students in elementary school SDN Luginasari I, II and Sukagalih VII Bandung City . - Nining Ningrum; Deru Marah Laut; Yenni Hendriyani Praptiwi (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2020)
ABSTRACTThe most effective efforts to prevent caries are brushing teeth regularly in the morning after breakfast and at night before sleeping with a good technique. Every child should get guidance brushing continuously, especially in children who do not have the ability to brush teeth properly. The role of parents is very necessary to guide their children at home, so that changes in children's behavior in maintaining healthy teeth and mouth can be achieved. The purpose of this study is to know the influence of the parents dental training to their pattern of guidance behaviour for teeth brushing first grade student at SDN Luginasari I, II and VII Sukagalih Bandung by measuring the increased of student’s hygiene index before and after training. This research is expected to be a guidance for the parents in conducting a good teeth brushing method for their children.This research is a quasi-experimental design with pre and post test. The study population was parents of the SDN Luginasari class I, II and VII Sukagalih Bandung, with a purposive sampling taken about 58 people. Analysis of data is using one tail t-tests dependent method. The results showed there was an increasing of Hygiene Index in children after the parents training. The children with criteria good HI was increase from 38% to 98%. Test one dependent tail t-test showed the results of the t-count larger than t-table so Ho rejected and Ha accepted. It can be concluded that is a significant effect of the parents dental training to their pattern of guidance behaviour for teeth brushing first grade student at SDN Luginasari I, II and VII Sukagalih Bandung.